Sejarah Revolusi Industri di Inggris Pada Tahun 1760-1830 - Mutiarawati Fajariah; Djoko Suryo (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The success of Europeans in creating their history has succeeded in bringing Europe to high success and culture, why is that: The period of renensaince in Europe began to emerge among the thinkers of scholars who can create new innovations and one of the very famous of the many is as we know it the industrial revolution, the industrial revolution that began in the United Kingdom. One of the industrial revolution happened because of population growth. The increase in population as it was waged, did not occur in England. This Industrial Revolution occurs because things that are diverse are better and healthier and have a general prosperity, scientific advances, especially technology used for life today such as technology in medical treatment, and technology in manufacturing such as in a casting and others-another by bricks discovered by russian scientist Thomas Newton, with this machine the changes that can be overcome in the life of social society this led to the industrial revolution and made Britain the first country of the industrial revolution.